THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING IN LEARNING INDONESIAN AT SD 002 SUNGAI SALAK - Susanti, Yenni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to improve learning outcomes in Indonesian through contextual teaching and learning model. This study was classroom action research conducted at SD 002 Sungai Salak involving 17 students. The results of this study showed that the teachers’ activity in meeting I of Cycle I was scored 53.57% with Good category. In meeting II of Cycle I, it increased to 71.43. Then, the score of teachers’ activit from meeting III to meeting IV increased by 3.57%. In addition, the score of students’ activity in meeting I of Cycle I was 50.00% with sufficient category. Then, in meeting II of Cycle I, it increased to 60.71%. In meeting II of Cycle II, the score of students’ activity was 75.00% with Good category, and in meeting IV of Cycle II, the score of students’ activity was 78.57% with Very Good category. Then, the students’ activities increased by 3.57% in meeting III and meeting IV. The students’ learning outcomes on Bahasa Indonesia increased after learning through Contextual Teaching and Learning model. The results of the test showed that the total score of of daily test was 1240 with the class average of 72.94 in which 11 students reached the target score while 6 students did not reach the target score. Meanwhile, the total score in Cycle II was 1420 with an average of 83.53 in which 15 students reached the target score and 2 students did not reach the tearget score.